Effect of thermal annealing treatments on the optical and electrical properties of aluminum-doped, amorphous, hydrogenated silicon carbide thin films - Sánchez Sovero, Luis Francisco (2019)
In this work, a systematic study of the structural, optical and electrical properties of aluminum doped hydrogenated amorphous silicon carbide (Al-doped a-SiC:H) thin films grown by radio frequency magnetron sputtering is presented. The samples were grown using a high purity Al and SiC targets in a hydrogen-rich atmosphere and then were subjected to a rapid thermal annealing processes with temperatures of up to 600 °C. The film thickness ranged from 321 nm to 266 nm. The amorphous nature of the thin films was confirmed by X-ray diffraction measurements before and after the annealing treatments. Fourier transform infrared spectroscopy analysis revealed the different heteronuclear bonds present in the samples, whilst Raman spectroscopy showed the different homonuclear bonds present in the material. The evolution of the latter bonds with annealing temperature was assessed, showing a change in the structure of the thin film. Energy-dispersive X-Rays Spectroscopy confirmed the incorporation of aluminum in the amorphous silicon carbide matrix. UV-VIS Transmittance spectra revealed optical parameters such as Tauc energy bandgap, Iso-absorption energy bandgap and refractive index. Furthermore, the bandgap is also determined by means of a recently developed band-fluctuation model. In addition, electrical resistivity is determined by means of a four-probe Van Der Pauw method. Only the samples annealed at 600 °C exhibited contacts with an Ohmic behavior. The annealed films exhibited lower resistivities than the as-deposited ones, probably due to a thermal-induced reordering of the atoms. This reordering is shown in the variation of the Urbach energy which is related to an increase in the Si-C bond density, due to the dissociation of the hydrogen-related bonds.